The Contribution of Indonesian International Student Mobility Awards (IISMA) on the Development of Employability Skills of Undergraduate Students in Indonesia - Dewanto, Nadira; Pritasari, Adita (Integrasi Sains Media, 2023)
Indonesia has the second highest youth unemployment rate among all ten ASEAN countries according to The World Bank Data in 2021, with 12% of the total unemployment rate dominated by bachelor graduates. One of the reasons behind youth unemployment in Indonesia is the mismatch between the skills possessed by university students and the labor market skills demand, referred to as the